National trends in pediatric ct scans in south korea: A nationwide cohort study - Kim, Nak Tscheol; Kwon, Soon Sun; Park, Moon Seok; Lee, Kyoung Min; Sung, Ki Hyuk (Journal of the Korean Society of Radiology, 2021)
Purpose This study evaluated the rates and annual trends of pediatric CT scans in South Korea using a nationwide population-based database. Materials and Methods Data regarding pediatric CT scan usage between 2012 and 2017 were retrieved from the health insurance review and assessment service. Data on the age, sex, diagnosis, and the anatomical area of involved patients were also extracted. Results A total of 576376 CT examinations were performed among 58527528 children aged below 18 years (9.8 scans/1000 children), and the number of CT examinations per 1000 children was noted to have increased by 23.2% from 9.0 in 2012 to 11.0 in 2017. Specifically, the number of CT examinations increased by 32.9% for the 6-12 years of age group (7.4/1000 to 9.8/1000) and by 34.0% for the 13-18 years of age group (11.4/1000 to 15.3/1000). Moreover, majority of the CT scans were limited to the head (39.1%), followed by the extremities (32.5%) and the abdomen (13.7%). Notably, the number of extremity CT scans increased by 83.6% (2.3/1000 to 4.2/1000), and its proportion as compared to other scans increased from 25.3% to 37.7%. Conclusion CT scans in the pediatric population increased continuously from 2012 to 2017 at an annual rate of 4.4%. Therefore, physicians should balance the benefits of CT with its potential harms from associated radiation exposure in pediatric patients.
Keywords: Child; Computed Tomography, X-Ray; Radiation